Barriers to the utilization of the Sehaty mobile health application in Saudi Arabia: a cross-sectional survey of non-healthcare users - Haitham Alzghaibi (Frontiers in Medicine)
IntroductionMobile health (mHealth) applications have the potential to enhance healthcare accessibility and management. However, several barriers continue to hinder their widespread adoption. In Saudi Arabia, the Sehaty app plays a critical role in national digital health efforts, yet little is known about the challenges faced by non-healthcare users.MethodsA cross-sectional survey was conducted among 403 non-healthcare users of the Sehaty app. Data were collected using a structured, validated questionnaire assessing ten categories of barriers: technical limitations, usability challenges, accessibility constraints, privacy and security concerns, communication and interaction difficulties, functionality restrictions, user satisfaction deficits, cost-related issues, time and productivity constraints, and inadequate support and training. Descriptive statistics, correlation analysis, and group comparisons using one-way ANOVA and t-tests were performed.ResultsTechnical issues such as frequent crashes and slow response times were reported as the most prominent barriers, significantly affecting user satisfaction. Usability challenges, including unintuitive navigation, were also widely reported. Privacy and security concerns—particularly regarding transparency and data protection—were major deterrents to app use. Accessibility constraints were more pronounced among older adults and those with disabilities, often compounded by limited support and training. Time inefficiencies and limited app functionality further reduced engagement. Cost-related barriers were minimal. Correlation analysis revealed strong associations among technical, usability, and functionality barriers, while demographic comparisons showed no significant differences across user groups.DiscussionThe findings underscore the need for comprehensive improvements to enhance the Sehaty app’s usability, reliability, security, and accessibility. Addressing these challenges through technical optimisation, user-centred design, enhanced data protection, and targeted training can support broader adoption and align the app’s development with Saudi Arabia’s Vision 2030 digital health goals.